The last card : inside George W. Bush's decision to surge in Iraq - Sayle, Timothy A. 2019- Herausgeber; Engel, Jeffrey A., 1972- 1972- Herausgeber; Brands, Hal, 1983- 1983- Herausgeber; Inboden, William 1972- Herausgeber (Cornell University Press, 2019)
"An oral history of President George W. Bush's decision to surge troops to Iraq, accompanied by scholarly analysis by leading scholars of international security and presidential history"--